2008
DOI: 10.1002/jnr.21600
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α receptor 1 deficiency enhances kainic acid–induced hippocampal injury in mice

Abstract: The exact role of TNF-alpha in excitotoxic neurodegeneration of the brain is unclear. To address this issue, the kainic acid (KA)-induced hippocampal injury model, a well-characterized model of human neurodegenerative diseases, was used in TNF-alpha receptor 1 (TNFR1)-knockout (TNFR1-/-) mice in the present study. After nasal application of a single dose of 40 mg of KA per kilogram body weight, TNFR1-/- mice showed significantly more severe seizures than the wild-type mice. In addition, obvious neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Moreover, this cytokine has also been shown to affect synaptic plasticity by inhibiting LTP (Tancredi et al, 1992;Cunningham et al, 1996;Butler et al, 2004) and by mediating synaptic scaling during activity blockade (Stellwagen and Malenka, 2006). TNF-alpha can also contribute to pathological conditions such as neurodegeneration (Ghezzi and Mennini, 2001;Saha and Pahan, 2003;Sriram and O'Callaghan, 2007;Tansey et al, 2007) and seizure activity (Bruce et al, 1996;Probert et al, 1997;Shandra et al, 2002;Yuhas et al, 2003;Meli et al, 2004;Balosso et al, 2005;Lu et al, 2008). In this respect, we demonstrated that injection of TNF-alpha in the mouse hippocampus exerts anticonvulsant effects on kainate seizures by interacting with the neuronal p75 receptors.…”
mentioning
confidence: 75%
“…Moreover, this cytokine has also been shown to affect synaptic plasticity by inhibiting LTP (Tancredi et al, 1992;Cunningham et al, 1996;Butler et al, 2004) and by mediating synaptic scaling during activity blockade (Stellwagen and Malenka, 2006). TNF-alpha can also contribute to pathological conditions such as neurodegeneration (Ghezzi and Mennini, 2001;Saha and Pahan, 2003;Sriram and O'Callaghan, 2007;Tansey et al, 2007) and seizure activity (Bruce et al, 1996;Probert et al, 1997;Shandra et al, 2002;Yuhas et al, 2003;Meli et al, 2004;Balosso et al, 2005;Lu et al, 2008). In this respect, we demonstrated that injection of TNF-alpha in the mouse hippocampus exerts anticonvulsant effects on kainate seizures by interacting with the neuronal p75 receptors.…”
mentioning
confidence: 75%
“…If similar trends are observed with kainate induced seizures, such result might directly suggest that glutamate release can be modulated by microglia to influence neuronal firing. In fact, evidence suggests that in kainate induced seizures, TNF-α may actually be neuroprotective (Balosso et al, 2005; Lu et al, 2008) and IL-1β is proconvulsant by enhancing glutamate (Vezzani et al, 1999; Vezzani et al, 2000). Future studies will also address behavioral outcomes from bilateral infusions of gancyclovir in order to incorporate activity from both sides of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α knockout worsens Listeria infection in the CNS [116] and TNF-α receptor knockout enhances the neuronal damage after excitotoxic [108, 117], ischemic [118] or traumatic injury [119]. Our study showed that mice lacking TNFR1 exhibited a more severe seizure activity, hippocampal neurodegeneration and increased microglial activation, suggesting that TNF - α plays its protective role through TNFR1 signaling [108], which is in agreement with a previous report [120]. Another study also proved that the protective roles of TNF - α in KA-induced neurodegeneration are via TNFR2 signaling [117].…”
Section: Altered Cytokine Expression Affects Ka-induced Injurymentioning
confidence: 99%